DESAIN VIDEO DENGAN APLIKASI PLOTAGON BERBASIS DENGAN PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Margareta; Utin Desy Susiaty; Wandra Irvandi (STKIP Subang, 2026)
The purpose of this study was to develop a differentiated learning-based video design to improve students' creative thinking skills on the topic of linear equations in one variable for eighth-grade students that is valid, practical, and effective. The research method employed was Research and Development (R&D) using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation.The findings of this study indicate that a differentiated learning-based video design was successfully developed. The developed video design had been validated by media experts and subject-matter experts. The validation results showed that the video design was suitable for use without revision. The video design was tested on eighth-grade students at SMP Negeri 13 Pontianak.Based on the results of student response questionnaires and teacher response questionnaires, the practicality level of the video design was categorized as very practical. Furthermore, based on the results of the creative thinking test administered to eighth-grade students, it can be concluded that the developed video design was effective.The implication of this study is that the video design can be further developed for other topics and subjects. In addition, training should be provided to teachers on how to create and utilize video designs that can attract students’ interest in learning and contribute positively to technological development.